2020
DOI: 10.1371/journal.pone.0234790
|View full text |Cite
|
Sign up to set email alerts
|

Increased functional dynamics in civil aviation pilots: Evidence from a neuroimaging study

Abstract: Civil aviation is a distinctive career. Pilots need to monitor the entire system in real time. However, the psychophysiological mechanism of flying is largely unknown. The human brain is a large-scale interconnected organization, and many stable intrinsic large-scale brain networks have been identified. Among them are three core neurocognitive networks: default mode network (DMN), central executive network (CEN), and salience network (SN). These three networks play a critical role in human cognition. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Changes in cognitive function after hypoxia exposure may be associated with brain function. Xu, Chen et al [5][6][7], conducted a series of functional imaging studies of pilots' brains in the resting and task states. Regarding structural magnetic resonance imaging (sMRI) research on pilots, a study conducted by Adamson MM studied the relationship between pilot flight training and the volume of the hippocampus [8].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in cognitive function after hypoxia exposure may be associated with brain function. Xu, Chen et al [5][6][7], conducted a series of functional imaging studies of pilots' brains in the resting and task states. Regarding structural magnetic resonance imaging (sMRI) research on pilots, a study conducted by Adamson MM studied the relationship between pilot flight training and the volume of the hippocampus [8].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies with pilots had shown that the functional MRI could depict the psychophysiological alterations of flying. The pilots exhibited better functional dynamics and cognitive flexibility ( Chen et al, 2020 ). In the current study, we focused on the cognitive function changes in cadets.…”
Section: Introductionmentioning
confidence: 99%